Online Learning Impacts on Academic Burnout: A Literature Review - Gita Aulia Nurani; Raissa Yulian Nafis; Afifah Nurfitria Ramadhani; Maharani Prastiwi; Naufal Hanif; Dio Ardianto (MO.RI Publishing, 2022)
Several reasons contribute to specific students' academic burnout due to the ongoing transformations in online learning. This literature review aims to determine how and to what extent students experienced burnout during the COVID-19 epidemic. Utilizing Google Scholar, 16 journals with the keyword